Multicomponent intranasal adjuvant for mucosal and durable systemic SARS-CoV-2 immunity in young and aged mice - Jangra, Sonia; Landers, Jeffrey J.; Laghlali, Gabriel; Rathnasinghe, Raveen; Warang, Prajakta; Park, Seok-Chan; O’Konek, Jessica. J.; Singh, Gagandeep; Janczak, Katarzyna W.; García-Sastre, Adolfo; Arya, Nandini; Karadag, Dilara; et al. (npj vaccines, 2023)
Multiple FDA-approved SARS-CoV-2 vaccines currently provide excellent protection against severe disease. Despite this, immunity can wane relatively fast, particularly in the elderly and novel viral variants capable of evading infection- and vaccination-induced immunity continue to emerge. Intranasal (IN) vaccination more effectively induces mucosal immune responses than parenteral vaccines, which would improve protection and reduce viral transmission. Here, we developed a rationally designed IN adjuvant consisting of a combined nanoemulsion (NE)-based adjuvant and an RNA-based RIG-I agonist (IVT DI) to drive more robust, broadly protective antibody and T cell responses. We previously demonstrated this combination adjuvant (NE/IVT) potently induces protective immunity through synergistic activation of an array of innate receptors. We now demonstrate that NE/IVT with the SARS-CoV-2 receptor binding domain (RBD), induces robust and durable humoral, mucosal, and cellular immune responses of equivalent magnitude and quality in young and aged mice. This contrasted with the MF59-like intramuscular adjuvant, Addavax, which showed a decrease in immunogenicity with age. Robust antigen-specific IFN-γ/IL-2/TNF-α was induced in both young and aged NE/IVT-immunized animals, which is significant as their reduced production is associated with suboptimal protective immunity in the elderly. These findings highlight the potential of adjuvanted mucosal vaccines for improving protection against COVID-19.